2015
DOI: 10.1080/19476337.2015.1099118
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of pork burger with added natural antioxidant based on extract of banana inflorescence (Musa cavendishii)

Abstract: (2016) Development and evaluation of pork burger with added natural antioxidant based on extract of banana inflorescence (Musa cavendishii), CyTA -Journal of Food, 14:2, 280-288, DOI: 10.1080/19476337.2015 To link to this article: https://doi.org/10. 1080/19476337.2015 This research evaluated the effect of the hydroethanolic extract of banana inflorescence (Musa cavendishii) and sodium erythorbate on the physicochemical and sensory characteristics and lipid stability of pork burgers during 120 days of storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…These data are in agreement with previous studies that show that meat discoloration is mostly due to a marked decrease in redness. In addition, a negative correlation (R = −0.634, P < 0.001) between redness and TBARS values was observed, in agreement with Schmidt et al (2016). In fact, Mancini and Hunt (2005) reported a decrease in redness in meat due to myoglobin oxidation and metmyoglobin accumulation.…”
Section: Physical and Chemical Parameterssupporting
confidence: 77%
“…These data are in agreement with previous studies that show that meat discoloration is mostly due to a marked decrease in redness. In addition, a negative correlation (R = −0.634, P < 0.001) between redness and TBARS values was observed, in agreement with Schmidt et al (2016). In fact, Mancini and Hunt (2005) reported a decrease in redness in meat due to myoglobin oxidation and metmyoglobin accumulation.…”
Section: Physical and Chemical Parameterssupporting
confidence: 77%
“…Banana inflorescence extract has been used in sausage and burger items. Pork patties have been treated with a 1–2 percent hydroethanolic extract of banana inflorescence [ 67 ]. The principal components, color features, pH, and sensory qualities of the burger product were not adversely affected by the addition of banana inflorescence extract.…”
Section: Banana Inflorescencementioning
confidence: 99%
“…For example, it has been reported that the decrease in pH can be a consequence of the presence of fatty acids and/or free amino acids in the medium, which are generated as a result of lipolysis or proteolysis that these foods may undergo. Additionally, a significant influence may be the accumulation of acidic secondary metabolites, such as lactic acid, which are formed during microbial growth [ 42 , 44 ]. On the other hand, high pH levels indicate the formation of basic substances, such as ammonia, which are also formed by microbial proteolysis [ 45 ].…”
Section: Effect Of Natural Leaf Extracts On the Quality Of Processed Meat Productsmentioning
confidence: 99%